Cover crop species can increase or decrease the fertilizer-nitrogen requirement in maize - Carciochi, Walter Daniel (2021)
Cover crop species and termination date could affect fertilizer-N management and N diagnostic methods traditionally used in bare fallow-maize (Zea mays L.) systems. Our objectives were to (a) assess the impact of cover crop termination date on maize yield and response to fertilizer-N, (b) determine maize yield at varying N rates following different cover crop species and mixtures, and (c) evaluate the chlorophyll meter reading (CMR), grain N concentration (Nc), and grain N nutrition index (NNI) as N diagnostic methods. Experiments were conducted at four sites in the southeastern Argentinean Pampas with maize planted after cover crops. Factors investigated were cover crops with vetch (Vicia villosa Roth), vetch-oat (Avena sativa L.) mixture, or bare fallow; early termination of cover crops or about 3 wk later; and maize fertilizer-N at 0, 50, 100, and 200 kg N ha–1. The minimum N rate that maximized grain yield was higher in vetch-oat mixture (100 kg N ha–1) than in vetch (50 kg N ha–1). Maize yield was not affected by cover crops with 200 kg N ha–1. Late termination dates of vetch-oat mixture reduced maize yield by 15% compared with early termination dates, while there was no effect of vetch termination date. Cover crop termination date did not affect yield response to fertilizer-N. Relative CMR at silking, grain NC, and especially grain NNI at maturity were useful tools to diagnose maize N status and cover crop effect. Cover crop management should be considered to adjust the fertilizer N rate and optimize maize productivity.